Brief report: Feasibility of a mindfulness and self‐compassion based mobile intervention for adolescents. (1st November 2016) - Donovan, Elizabeth; Rodgers, Rachel F.; Cousineau, Tara M.; McGowan, Kayla M.; Luk, Stephanie; Yates, Kayla; Franko, Debra L.
ABSTRACT: The aim of the study was to test the feasibility of a mindfulness and self‐compassion based program for adolescents, to be delivered though mobile phones. Twenty racially and ethnically diverse US adolescents enrolled in a study to use the app for 30 days, after which they provided satisfaction data and participated in focus groups to describe their experiences and offer suggestions for improving the app. Usage data were also captured. Results indicated that participants used the app on the majority of days over the intervention period, reported finding it helpful for managing stress, and provided suggestions for substantive areas for improvement. These findings suggest that a mobile app may be a feasible way to disseminate a mindfulness and selfcompassion based program widely among adolescents.